Literature Review: The Country of Origin Image Affecting Consumers’ Purchase Decision - Zhanerke Kurmangali (International Journal of Engineering and Management Research, 2019)
The country of origin image is considered as one of the most important factor for consumers when they make a purchase decision. A lot of marketers and scholars have researched this factor from different perspectives. The country of origin image may ease consumers’ evaluation of the product when they would like to buy unknown product from foreign country. In addition, many aspects can affect country of origin image and the latter can make an impact on consumers’ perception of goods. The purpose of the paper to review existing literature for more accurate understanding of the “country origin image” factor and to analyze its effect on consumers’ purchase decision. This study explores consumers’ perception about country’s image from different kind of variables additionally by giving examples to make it clearer for readers. This study also shares the personal opinion about future concept of “country of origin image” as a factor consumers’ purchase behavior.